2020
DOI: 10.1111/hel.12740
|View full text |Cite
|
Sign up to set email alerts
|

Review: Prevention and management of gastric cancer

Abstract: Gastric cancer (GC) is still the fifth most frequently diagnosed cancer and the third leading cause of cancer deaths in both sexes worldwide. Although the incidence of GC is predicted to continue declining in a growing number of countries in the future, on a global scale the number of newly diagnosed GC cases will remain high, or increase even further, due to changes in population size and increasing risks observed in younger generations. In a retrospective cohort study, collecting data from the Veterans Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…Indeed, in our cohort, 34.5% of GC patients were younger than 60 years at the time of diagnosis and 45.1% of them presented with alarm symptoms. Recently, a registry-based study with data on GC incidence by year of diagnosis, gender, and age from 92 cancer registries in 34 countries, have shown alarming incidence increases in younger age groups (below 50 years of age) in both low-incidence and high-incidence populations [34,35]. Based on our data and the current epidemiological facts, alarm symptoms should not be underestimated irrespective of the age of the patient, nor should endoscopy be neglected.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, in our cohort, 34.5% of GC patients were younger than 60 years at the time of diagnosis and 45.1% of them presented with alarm symptoms. Recently, a registry-based study with data on GC incidence by year of diagnosis, gender, and age from 92 cancer registries in 34 countries, have shown alarming incidence increases in younger age groups (below 50 years of age) in both low-incidence and high-incidence populations [34,35]. Based on our data and the current epidemiological facts, alarm symptoms should not be underestimated irrespective of the age of the patient, nor should endoscopy be neglected.…”
Section: Discussionmentioning
confidence: 55%
“…1 Approximately 1 million new cases of stomach cancer are diagnosed globally each year. 2 China is the country most affected by gastric cancer, accounting for 42.6% of the global incidence and 45% of all gastric cancer-related deaths. 3 Surgery is currently required to cure gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…5 Currently, more and more randomized clinical trials have shown that preoperative and postoperative therapy can improve the prognosis of patients with LAGC. 2,3,6,7 Neoadjuvant therapy in particular is increasingly being accepted and performed by clinicians. An increasing number of neoadjuvant chemotherapy regimens for LAGC have been proven to have good efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Both Western and Eastern Asia account for majority of cases worldwide, while Asian-Americans have a 5 times higher incidence, than other groups in the United States (6,7). The most common cause of gastric cancer remains Helicobacter Pylori infection, followed by chronic gastritis and diet (8). Pathologic sub-classification indicates that the most common types are adenocarcinomas and are also further classified into intestinal type associated with metaplasia and diffuse type associated with signet ring cells and linitis plastica (9).…”
Section: Introductionmentioning
confidence: 99%